ANALISIS KEMAMPUAN MAHASISWA MERANCANG PEMBELAJARAN SASTRA INDONESIA PADA MATA KULIAH TEORI DAN PRAKTIK PENGAJARAN SASTRA INDONESIA - Tri Astuti; Dwi Desi Fajarsari; Ajeng Tina Mulyana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The ability to design literature instruction is a crucial competency for prospective Indonesian language and literature teachers, given that literature instruction emphasizes appreciation, expression, and the internalization of values. This study addresses the gap between students' conceptual mastery of literature teaching theories and their practical ability to design literature lessons suitable for the classroom. The study aims to describe and analyze students' abilities in designing Indonesian literature lessons within the